Results of quality studies of spring waters of the Republic of Tatarstan - Lilia I. Almitova; Venera I. Makaeva; Alsu R. Makaeva (Водное хозяйство России: проблемы, технологии, управление)
The study of springs is of great scientific and practical interest, because the population increasingly prefers to use spring water as an alternative source of drinking water/